ANALISIS TENTANG ORIENTASI POLITIK PADA MAHASISWA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Wilandri, Yastika; Erlinda, Sri; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by problems that arise during observations made by researchers, namely Pancasila and Citizenship Education students as if indifferent in politics in Indonesia. Pancasila and Citizenship Education students currently basically only know a small part of the world of politics, which is in the form of the latest policy making and popular political issues through the mass media. However, Pancasila Education and citizenship students are reluctant to know more because of the lack of student confidence in political changes that are usually influenced by the interests of certain political actors. Riau University Education? The purpose of this research is to find out how the political orientation of the Pancasila and Citizenship Education Study Program Students of the Teaching and Education Faculty of Riau University. This research was conducted in the Pancasila and Citizenship Education Study Program of the Teaching and Education Faculty of Riau University in May - September 2019. This research used a quantitative descriptive method. The population in this study was the Pancasila and Citizenship Education Study Program Students of the Teaching and Education Faculty of Riau University in 2016, 2017, 2018. The sample in this study was taken using proportional sampling technique. The overall research of political orientation is 84% which means